EVALUATION OF OXIDATIVE STRESS IN PATIENTS WITH ORAL SQUAMOUS CELL CARCINOMA - SUNI ANN THOMAS; SETHUPATHY.S (International Journal of Pharma and Bio Sciences, 2015)
Oral Squamous Cell Carcinoma (OSCC) is one of the most common malignancies in India and thus there is a need for prognostic markers as it can make a crucial contribution to the prediction of outcome. In diseased condition, body can enhance the endogenous defense mechanism. However, it has been observed that whenever the level of the cellular antioxidant system goes down or reactive oxygen species reach abnormally high levels, oxidative damage to the cell occurs, which subsequently lead to several pathological conditions including cancer. We designed this study to evaluate the oxidative stress and antioxidant levels in OSCC patients. TBARS levels were increased, whereas the endogenous antioxidant levels were found to be declined in patients with oral cancer. As the disease progresses from precancerous to cancerous state, levels of antioxidants declined further. Hence, these antioxidant markers would be suitable for predicting the prognosis of oral cancer.